Gambaran Tingkat Pengetahuan Mengenai Gejala dan Pencegahan Konjungtivitis di Puskesmas Wori - Aurelia Hanna Chriesty Rundengan; Rillya Dianne Paulani Manoppo; Imelda Helena Martina Najoan (Green Publisher Indonesia, 2026)
Background: Conjunctivitis is one of the most common ocular complaints encountered in primary healthcare settings, as the conjunctiva being directly exposed to the external environment is highly susceptible to irritation and infection. Although it is not a major cause of severe visual impairment, conjunctivitis frequently prompts individuals to seek medical attention. Several studies have reported a high incidence of conjunctivitis, including research at the Provincial Eye Hospital of North Sulawesi which found that 42.31% of ocular infections were conjunctivitis. Preliminary interviews at Wori Public Health Center revealed that conjunctivitis cases occur every month, yet the community’s level of knowledge varies widely. This variation highlights the need for research to assess the community’s knowledge regarding the symptoms and prevention of conjunctivitis as a basis for developing more effective health education. Objective: To determine the level of knowledge regarding the symptoms and prevention of conjunctivitis among individuals visiting Wori Public Health Center. Methods: This study employed a quantitative method with a descriptive design and a cross-sectional approach involving 97 respondents. Results: Knowledge regarding conjunctivitis symptoms was predominantly in the good category, with 74 respondents (76.2%) achieving a total score of 88.7%. Knowledge regarding prevention was also mostly in the good category, with 64 respondents (66%) scoring 83.2% in total. Conclusion: The level of knowledge among individuals visiting Wori Public Health Center regarding the symptoms and prevention of conjunctivitis is generally good, as indicated by the predominance of respondents within the good knowledge category, although a small proportion still demonstrated moderate and low knowledge levels.